FoxP3 Tregs Response to Sublingual Allergen Specific Immunotherapy in Children Depends on the Manifestation of Allergy - Anna Stelmaszczyk-Emmel; Anna Zawadzka-Krajewska; Eliza Głodkowska-Mrówka; Urszula Demkow (Journal of Immunology Research)
Over the last decades allergic diseases has become a major health problem worldwide. The only specific treatment to date is allergen specific immunotherapy (ASIT). Although it was shown that ASIT generates allergen-tolerant T cells, detailed mechanism underlying its activity is still unclear and there is no reliable method to monitor its effectiveness. The aim of our study was to evaluate ASIT influence on the frequency of forkhead box P3 (FoxP3) Tregs in allergic children with various clinical manifestations. The relative number of FoxP3 Tregs in 32 blood samples from allergic children at baseline and/or after 1 year of ASIT was assessed by flow cytometry. In the entire studied group, the percentage of FoxP3 Tregs did not increase 1 year after ASIT. Nevertheless, the percentage of FoxP3 Tregs after ASIT significantly increased in children with respiratory allergy (conjunctivitis, asthma, and rhinitis) coexisting with nonrespiratory manifestations (food allergy and/or atopic dermatitis), whereas, in patients with respiratory allergy only, the percentage of FoxP3 Tregs decreased. To the best of our knowledge, this is the first report showing various differential FoxP3 Tregs response to ASIT in allergic children. FoxP3 Tregs number could be useful in treatment monitoring. Further studies are warranted to confirm these observations.